Discurso improvisado e a prática dos eixos curriculares do ensino religioso em escolas públicas do Recife - PE - Santos, Romilda Soares dos (2014)
When referring to education, it is interesting to know that it is related to a set of procedures designed to lead individuals to develop the educational dimension in your life, enabling them to produce culture, and at the same time, take ownership of the goods culture ever produced. The school that we must ensure all the cultural and scientific training for the personal life, professional and citizen, allowing an autonomous, critical and constructive relationship with the culture in its manifestations, whether provided by science, art, the aesthetic culture, ethics and even the parallel culture (mass media), is the everyday culture. Have Religious Education (RE) , in turn , has the general goal to work the Religious Phenomenon comprehensive and interdisciplinary way and with reference to the axes of Religious Education Curriculum that will guide their enforcement and effective practice in Elementary Education (LDB , 9.394/96) . Religious Education is a curricular component that discusses the diversity and complexity of the human being as open to various perspectives of the Sacred, present in time and cultural spaces in relation to human existential walking person. Directs the student in order to have a critical consciousness and a broad worldview and provide a systematic study of religion as a historical institution working human being in search of Transcendence. The school, in short, is committed to helping students become subjects of accurate reflection , able to construct categories of understanding and critical appropriation of reality . Hence , our concern in questioning some positions concerning Religious Education classes , seeking to address its history from the beginnings to the present day , aiming thereby to understand issues such as : Improvisation of Religious Education , Training Professionals in Religious Education Religious Education classes as Supplementary Hours and even ignorance itself, in general, the five Axis Guiding ( content) of the National Curriculum Parameters of Religious Education teachers of this discipline . The methodology consisted of a bibliographic record keeping and research field , through an open questionnaire applied to a sample of twenty teachers from the selected schools ( Enchanted Lagoon and Mission St. Benedict ) , on the themes : values formation , critical reflection and a healthy human coexistence cidadã.Com the questionnaire , we obtained a range of problems : Problems with discipline " Religious Education" Lack of adequate training and ability to work Lack of discipline , there is a gap between curriculum proposals and operational , emerging, often a Speech improvised. Recognizing its limitations as regards their training and working condition , the subjects of the sample expressed their willingness / and the open / to the implementation of training Courses by the competent bodies of the Department of Education and formations to dispel doubts , exceed the needs and difficulties impeding the minister of Religious Education course . We hope that the issues discussed in this dissertation contributes to the reflection of Religious Education as a whole!